Catholic Cathedral, Reykjavik, Iceland (1940)
Photo of the Cathedral Basilica of Christ the King, a neo-Gothic Catholic church in Reykjavik, completed in 1929. Possibly taken by Waldo Ruess in the 1940s or 1950s.